The Effect of Budget Oversight, Organizational Commitment, and Human Resource Quality on the Quality of Government Financial Reporting with the Government Internal Control System as an Intervening Variable - Akram, Miftachul; Islahuddin, Islahuddin; BZ, Fazli Syam (Jurnal Ekonomi dan Bisnis Digital, 2024)
This research examines the impact of budget oversight, organizational commitment, and human resource quality on the quality of government financial reporting, with internal control systems serving as a mediating variable. Data were collected from municipal governments using quantitative methods. The analysis employs direct and indirect effect tests, including Sobel and Bootstrap methods, to assess mediation. Results reveal that budget oversight, organizational commitment, and human resource quality positively impact financial reporting quality directly and through the internal control system. These findings underscore the need to enhance budget oversight, organizational commitment, and human resource quality to improve government financial accountability and transparency.